1991
DOI: 10.1161/01.str.22.8.971
|View full text |Cite
|
Sign up to set email alerts
|

A review of hemoglobin and the pathogenesis of cerebral vasospasm.

Abstract: We believe that current experimental and clinical evidence can be most satisfactorily interpreted by assuming that oxyhemoglobin is the cause of cerebral vasospasm that follows subarachnoid hemorrhage. We review the pathogenetic mechanisms by which oxyhemoglobin affects cerebral arteries. The relative importance of each of these mechanisms in the genesis of vasospasm, the biochemical pathways of oxyhemoglobin-induced smooth muscle contraction, and the intracellular actions of oxyhemoglobin on smooth muscle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
324
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(341 citation statements)
references
References 191 publications
13
324
0
4
Order By: Relevance
“…Since the heparinized blood (containing 100 U ml À1 heparin) can be assumed to be almost completely devoid of the activity of thrombin and other heparin-sensitive proteinases, the heparin-sensitive proteinases could not account for all mechanisms for the induction of hyper-responsiveness. Known spasmogens such as platelet products (Yanamoto et al, 1992;Tosaka et al, 2001) and free radicals (Macdonald and Weir, 1991) could be other factors contributing to induction of the upregulation of PAR 1 and hyper-contractile responsiveness. Such factors, however, remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the heparinized blood (containing 100 U ml À1 heparin) can be assumed to be almost completely devoid of the activity of thrombin and other heparin-sensitive proteinases, the heparin-sensitive proteinases could not account for all mechanisms for the induction of hyper-responsiveness. Known spasmogens such as platelet products (Yanamoto et al, 1992;Tosaka et al, 2001) and free radicals (Macdonald and Weir, 1991) could be other factors contributing to induction of the upregulation of PAR 1 and hyper-contractile responsiveness. Such factors, however, remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of spasmogens (Macdonald and Weir, 1991;Tosaka et al, 2001) and/or increased vascular responsiveness (Harder et al, 1987;Todo et al, 1998;Sato et al, 2000) is considered to contribute to the development of vasospasm. A clinical study demonstrated that the incidence of post-haemorrhagic vasospasm correlates with the amount of peri-arterial blood clotting (Fisher et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…That is, delayed vasospasm is maximal at about a week after SAH at a time when CSF levels of Hb are low. Nevertheless, if Hb concentrations were very high in the clot immediately adjacent to blood vessels, and are substantially different than what is detected in the CSF, Hb could contribute to delayed vasospasm in brain after SAH (Janjua and Mayer, 2003;Macdonald and Weir, 1991).…”
Section: Two Classes Of Compounds That Could Cause Vasospasmmentioning
confidence: 97%
“…16) Cerebral vasospasm is associated with decreased local synthesis of nitric oxide (NO) caused by disturbed endothelial NO synthetase activity due to endothelial cell damage. Local concentrations of NO are also reduced due to the high binding affinity with oxyhemoglobin (oxyHb) derived from the subarachnoid clot around the brain surface and major blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Local concentrations of NO are also reduced due to the high binding affinity with oxyhemoglobin (oxyHb) derived from the subarachnoid clot around the brain surface and major blood vessels. 16,17) NO is involved in the regulation of the cerebral circulation, and is accepted as the most effective relaxing agent for the cerebral arterial network, and participates in the maintenance of resting cerebrovascular tone. 7,8) Depletion of NO is thought to be important in the pathogenesis of cerebral vasospasm.…”
Section: Introductionmentioning
confidence: 99%